Effect of Dilute Sulphuric Acid Pretreatment on Cellulase Production by Bacillus subtilis (K-18) through Response Surface Methodology: Cellulase Production by Bacillus subtilis in Submerged Fermentation - Arooj, Anam; Irfan, Muhammad; Tabbasum, Fouzia; Shakir, Hafiz Abdullah; Qazi, Javed Iqbal (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
The present study investigated the optimization of dilute sulphuric acid pretreatment to maximize cellulase production from banana peduncle waste through Box-Behnken design of response surface methodology. Cellulase production was carried out in 250ml capacity Erlenmeyer flask using pretreated banana peduncle as substrate in submerged fermentation by Bacillus subtilis K-18 incubateda t 50o C for fermentation period of 24 h. Results indicated that chemical pretreatment using sulphuric acid favored cellulase production as compared to thermochemical pretreatment using sulphuric acid followed by autoclaving at 121o C for 15 min and 15 psi. Maximum Filter Paper activity of 0.958 IU/ml/min was observed at optimal pretreatment conditions of 0.4 N H2SO4 concentration, 15% substrate concentration and residence time of 6h with chemical pretreatment. For thermochemical pretreatment optimal FPase activity of 0.63 IU/ml/min was recorded at 0.4 N H2SO4 concentration, 10% substrate concentration and residence time of 4 h. The proposed regression model for both types of pretreatments was found significant as revealed by F-value, P-value and coefficient of determination. These results indicated that banana peduncle can be successfully utilized as solid substrate in submerged fermentation for cellulase enzyme production.